Self-assembled supramolecular modified chitosan composite material as well as preparation method and application thereof

A self-assembled supramolecular chitosan composite material addresses skin microecological imbalance and inflammation by enhancing interlayer spacing and surface charge, achieving effective antibacterial and anti-inflammatory properties.

CN119219993AActive Publication Date: 2024-12-31DONGGUAN JUWEI NEW MATERIAL TECH CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411314457.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2024-12-31
Estimated Expiration
2044-09-20

AI Technical Summary

Technical Problem

Excessive sebum secretion leads to skin microecological imbalance, inflammation, and damaged skin barrier due to dirt and microorganism accumulation, necessitating materials with barrier repair functions to improve skin health.

Method used

A self-assembled supramolecular modified chitosan composite material composed of carboxymethyl deacetylated chitosan and cationic polymer-modified sodium bentonite, which undergoes supramolecular self-assembly, enhancing interlayer spacing and surface charge for improved antibacterial and anti-inflammatory effects.

Benefits of technology

The composite material effectively inhibits harmful bacteria, regulates skin microecology, and reduces inflammation by maintaining structural stability and synergistic effects between components, with specific inhibitory concentrations against key skin flora.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119219993A_ABST
    Figure CN119219993A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of daily chemicals, and particularly discloses a self-assembled supramolecular modified chitosan composite material as well as a preparation method and application thereof. The self-assembled supramolecular modified chitosan composite material is prepared from the following components in percentage by mass: 10 to 20 percent of carboxymethyl deacetylated chitosan, 0.2 to 1.0 percent of cationic polymer modified sodium bentonite and the balance of water. Carboxymethyl deacetylated chitosan and cationic polymer modified sodium bentonite are compounded, in the mixing process, the carboxymethyl deacetylated chitosan and the cationic polymer modified sodium bentonite are subjected to supramolecular self-assembly, and the carboxymethyl deacetylated chitosan is orderly intercalated into the cationic polymer modified sodium bentonite, so that the cationic polymer modified sodium bentonite is prepared. The self-assembled supramolecular modified chitosan composite material finally shows good effects of improving scalp micro-ecology, repairing skin and reducing skin inflammation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of daily chemicals, and in particular to a self-assembled supramolecular modified chitosan composite material and a preparation method and application thereof. Background Art

[0002] With the improvement of living standards, people's pace of life is getting faster and faster, and work pressure is also increasing; in addition, with age, a large proportion of the population has problems with excessive sebum secretion on the skin (including the scalp). Excessive sebum secretion can easily lead to the accumulation of dirt, especially fat-soluble organic matter and many kinds of microorganisms, which can easily cause bacteria, fungi, viruses, etc. to penetrate directly and cause infection, thereby leading to inflammatory reactions, making the skin prone to problems such as skin microecological imbalance, inflammation, and damaged skin barrier.

[0003] Therefore, there is an urgent need to provide raw materials with barrier repair functions to improve the skin's microecology, repair the skin, and reduce skin inflammation. Summary of the invention

[0004] The purpose of the present application is to overcome the deficiencies of the above-mentioned prior art and to provide a self-assembled supramolecular modified chitosan composite material and a preparation method and application thereof. The self-assembled supramolecular modified chitosan composite material designed by the present application can improve the scalp microecology, repair the skin and reduce skin inflammation.

[0005] To achieve the above purpose, the technical solution adopted by this application is:

[0006] The present application provides a self-assembled supramolecular modified chitosan composite material, which comprises, by mass percentage, the following:

[0007] 10-20% carboxymethyl deacetylated chitosan, 0.2-1.0% cationic polymer modified sodium bentonite and the balance water.

[0008] Supramolecular molecules usually refer to complex organized aggregates composed of two or more molecules bound together by intermolecular interactions, while maintaining a certain integrity, giving them clear microstructures and macroscopic properties.

[0009] The present invention compounds carboxymethyl deacetylated chitosan and sodium bentonite modified by a cationic polymer. During the mixing process, the carboxymethyl deacetylated chitosan and the sodium bentonite modified by the cationic polymer undergo supramolecular self-assembly, and the carboxymethyl deacetylated chitosan is intercalated into the sodium bentonite modified by the cationic polymer in an orderly manner, thereby obtaining a self-assembled supramolecular modified chitosan composite material.

[0010] Among them, the spacing between bentonites in the sodium bentonite modified by cationic polymer increases, and carboxymethyl deacetylated chitosan molecules can more easily enter the intercalation structure of bentonite. Carboxymethyl deacetylated chitosan and sodium bentonite modified by cationic polymer maintain structural stability through hydrogen bonds and van der Waals forces, and the final product has good stability.

[0011] In the self-assembled supramolecular modified chitosan composite material of the present application, after the bentonite is modified, not only the interlayer spacing of the bentonite becomes larger, but also the surface of the bentonite has a certain positive charge, so that after the subsequent assembly with carboxymethyl deacetylated chitosan, there is a synergistic effect between the sodium bentonite modified by the cationic polymer and the carboxymethyl deacetylated chitosan, and the final product shows a good effect of improving the scalp microecology (specifically, the antibacterial concentration for Staphylococcus epidermidis is >100000 mg / kg, the minimum inhibitory concentration for Propionibacterium acnes is <9200 mg / kg, and the minimum inhibitory concentration for Malassezia furfur is <3800 mg / kg), repairing the skin and reducing skin inflammation.

[0012] As a preferred embodiment of the self-assembled supramolecular modified chitosan composite material described in the present application, the weight average molecular weight of the carboxymethyl deacetylated chitosan is 100 kDa to 180 kDa, and the degree of deacetylation is 70 to 95%.

[0013] The present application adopts carboxymethyl deacetylated chitosan with a weight average molecular weight and a degree of deacetylation within the above-mentioned range. The sodium bentonite modified by the cationic polymer has good dispersibility in the carboxymethyl deacetylated chitosan solution. The self-assembled supramolecular modified chitosan composite material finally prepared is not prone to precipitation and stratification. The product quality is better and is more conducive to the product improving the scalp microecology, repairing the skin and reducing skin inflammation.

[0014] When the weight average molecular weight of carboxymethyl deacetylated chitosan is lower than 100 kDa, the viscosity of the obtained carboxymethyl deacetylated chitosan solution is low, and the final product is prone to the phenomenon of modified bentonite precipitation and stratification after being placed for a period of time. When the weight average molecular weight of carboxymethyl deacetylated chitosan is higher than 180 kDa, the viscosity of the obtained carboxymethyl deacetylated chitosan solution is too high, and the sodium bentonite modified by the cationic polymer is not easy to disperse in the chitosan solution, resulting in poor quality of the final product (improving scalp microecology, repairing skin and reducing skin inflammation, etc.).

[0015] Moreover, chitosan is the product of chitin after deacetylation. The degree of deacetylation determines the content of amino groups on the polysaccharide molecular chain. The lower the degree of deacetylation, the more difficult it is for chitosan to dissolve in water. However, the higher the degree of deacetylation, the more charged groups are generated by the protonation of amino groups in the dilute acid solution, resulting in changes in its structure and differences in properties. Therefore, the degree of deacetylation of the carboxymethyl deacetylated chitosan used in this application should be controlled between 70 and 95%.

[0016] As a preferred embodiment of the self-assembled supramolecular modified chitosan composite material described in the present application, the particle size of the sodium bentonite modified by the cationic polymer is 30 to 80 μm.

[0017] The cationic polymer-modified sodium bentonite of the present application adopts the above-mentioned particle size. When the particle size of the cationic polymer-modified sodium bentonite is less than 30 μm, not only the grinding cost increases sharply, but also in the subsequent self-assembly reaction, the cationic polymer-modified sodium bentonite particles with too small particle size are easily agglomerated due to electrostatic action, and carboxymethyl deacetylated chitosan is not easy to be intercalated into the interlayer structure of bentonite; when the particle size of the cationic polymer-modified sodium bentonite is greater than 80 μm, the particle size of the cationic polymer-modified sodium bentonite is too large. After being prepared into the final product, the cationic polymer-modified sodium bentonite is easily precipitated, and the product is unstable.

[0018] As a preferred embodiment of the self-assembled supramolecular modified chitosan composite material described in the present application, the cationic polymer includes at least one of polyquaternium-11, polyquaternium-16, polyquaternium-24, polyquaternium-28, polyquaternium-37 and polyquaternium-73.

[0019] By using the above-mentioned cationic polymers, the performance of the self-assembled supramolecular modified chitosan composite material in improving scalp microecology, repairing skin and alleviating inflammation can be improved, as well as the stability can be improved.

[0020] As a preferred embodiment of the self-assembled supramolecular modified chitosan composite material described in the present application, the preparation method of the cationic polymer modified sodium bentonite comprises the following steps:

[0021] 1) Mixing bentonite with water, stirring and then standing, and removing the upper layer solution to obtain washed bentonite;

[0022] 2) adding the sodium salt solution to the washed bentonite prepared in step 1), stirring and then standing, and removing the upper layer of solution to obtain sodium bentonite;

[0023] 3) Soaking the sodium bentonite prepared in step 2) in a cationic polymer solution, stirring and then standing, removing the upper solution, and then calcining at high temperature and ball milling to obtain the cationic polymer-modified sodium bentonite.

[0024] The purpose of modifying bentonite in the present application is to improve the performance and stability of the self-assembled supramolecular modified chitosan composite material.

[0025] In the technical solution of the present application, commercially available bentonite (usually calcium-based bentonite) usually contains more impurities. However, the final product of the present application is a suspension. The presence of these impurities can easily affect the stability and performance of the final product. Therefore, the use of water washing in step 1) is beneficial to reduce the impurities in the sodium bentonite modified by the cationic polymer and improve the performance and stability of the final product.

[0026] In the present application, through step 2), commercially available bentonite is soaked in a sodium salt solution, and sodium ions enter the interlayer structure of the bentonite, replacing the calcium ions therein, thereby reducing the van der Waals force between the layers, increasing the interlayer spacing, and improving the adsorption, cation exchange and water absorption and swelling properties of the bentonite, thereby obtaining sodium bentonite; compared with calcium-based bentonite, the interlayer spacing of the sodium bentonite is larger, and its adsorption, cation exchange and water absorption and swelling properties are better than those of calcium-based bentonite.

[0027] Furthermore, the sodium bentonite is further modified with a cationic polymer through step 3), and the cationic polymer exhibits weak acidity, which can further weaken the van der Waals force between layers and increase the interlayer spacing. In addition, after the cationic polymer modification, the bentonite exhibits a certain positive charge. When it is subsequently compounded with a carboxymethyl deacetylated chitosan solution, the bactericidal performance of the final product can be further improved, and the performance of the final product in improving the scalp microecology, repairing the scalp and reducing inflammation can be enhanced.

[0028] Furthermore, through the high temperature activation treatment and ball milling treatment steps of step 3), the high temperature activation treatment can bring out the water on the surface of bentonite and the bound water in the framework, thereby improving the porosity and adsorption performance of bentonite. Bentonite after high temperature activation is often prone to caking. Compared with ordinary grinding treatment, ball milling treatment adds grinding balls during the grinding process, which can fully grind the caking bentonite into fine bentonite particles, and the subsequent bentonite is also more likely to self-assemble with carboxymethyl deacetylated chitosan to form a supramolecular structure.

[0029] The cationic polymer-modified sodium bentonite obtained by the above-mentioned steps can inhibit the growth of harmful bacteria, has a good effect of regulating microecology, and can also improve the anti-inflammatory and repair effects.

[0030] Preferably, the sodium salt solution is a sodium salt solution that is neutral (pH is about 7) after being dissolved in water; the sodium salt solution is at least one of sodium sulfate, sodium bisulfate, sodium chloride, and sodium nitrate solution.

[0031] The present application adopts the above-mentioned types of sodium salt solutions, cationic polymers and their concentrations, which can better improve the stability of the self-assembled supramolecular modified chitosan composite material, which is beneficial to the effects of the self-assembled supramolecular modified chitosan composite material in improving scalp microecology, repairing skin and reducing skin inflammation.

[0032] As a preferred embodiment of the self-assembled supramolecular modified chitosan composite material described in the present application, in step 1), the mass ratio of the bentonite to water is 1:(4-8); in step 2), the mass ratio of the washed bentonite to the sodium salt solution is 1:(4-8); in step 3), the mass ratio of the sodium bentonite to the cationic polymer solution is 1:(4-8).

[0033] As a preferred embodiment of the self-assembled supramolecular modified chitosan composite material described in the present application, the concentration of sodium ions in the sodium salt solution is 1-3 mol / L, and the concentration of cationic polymer in the cationic polymer solution is 0.5-2 wt%.

[0034] When the concentration of the cationic polymer in the cationic polymer solution is too high, the amount of cationic polymer attached to the surface of bentonite will increase. Chitosan itself is also a polymer, and the increase in cationic polymer will make it more difficult for chitosan to be intercalated into bentonite.

[0035] As a preferred embodiment of the self-assembled supramolecular modified chitosan composite material described in the present application, in the step 1), the stirring time is 30 to 90 minutes, the stirring speed is 80 to 150 rpm, and the standing time is 60 to 120 minutes;

[0036] In the step 2) and step 3), the stirring time is 3 to 5 hours, the stirring speed is 80 to 150 rpm, and the standing time is 60 to 120 minutes;

[0037] In the step 3), the calcination temperature is 130-200° C., and the calcination time is 90-150 min.

[0038] In the technical solution of the present application, the temperature of the calcination treatment should not be too high or too low, and should be controlled between 130 and 200°C. When the calcination temperature is lower than 130°C, the surface water of the bentonite and the bound water in the framework are not easily brought out, which is not conducive to subsequent self-assembly. When the calcination temperature is higher than 200°C, the cationic polymer attached to the surface of the bentonite is prone to structural changes or even carbonization, which is not conducive to the preparation of self-assembled supramolecular modified chitosan composite materials.

[0039] The present application also provides a method for preparing the self-assembled supramolecular modified chitosan composite material, comprising the following steps:

[0040] (1) mixing water and carboxymethyl deacetylated chitosan uniformly to obtain a carboxymethyl deacetylated chitosan solution;

[0041] (2) mixing the carboxymethyl deacetylated chitosan solution and the sodium bentonite modified by the cationic polymer, and subjecting the mixture to high-speed shear dispersion treatment and ultrasonic treatment to obtain a self-assembled supramolecular modified chitosan composite material;

[0042] The rotation speed of the high-speed shearing and dispersing treatment is 6000-12000 rpm, and the time of the high-speed shearing and dispersing treatment is 20-40 min;

[0043] The power of the ultrasonic treatment is 400-800W, and the time of the ultrasonic treatment is 40-80min.

[0044] In the technical solution of the present application, the viscosity of the carboxymethyl deacetylated chitosan solution is relatively high. After the cationic polymer-modified sodium bentonite is added, it is difficult to separate the cationic polymer-modified sodium bentonite in the carboxymethyl deacetylated chitosan solution by conventional stirring treatment, and it is difficult to self-assemble to form supramolecules. The cationic polymer-modified sodium bentonite is easy to precipitate, resulting in deterioration of product quality. For example, the product's antibacterial effect on Propionibacterium acnes and Malassezia furfur is reduced, and the anti-inflammatory and skin repair effects are also reduced.

[0045] High-speed shear dispersion treatment can evenly disperse the sodium bentonite modified by the cationic polymer in the carboxymethyl deacetylated chitosan solution, which is beneficial to the self-assembly of the sodium bentonite modified by the cationic polymer and the carboxymethyl deacetylated chitosan solution to form a supramolecular structure.

[0046] In the technical solution of the present application, ultrasonic treatment can discharge bubbles in the preparation process of the self-assembled supramolecular modified chitosan composite material, thereby improving the stability of the final product.

[0047] The present application also provides the use of the self-assembled supramolecular modified chitosan composite material in the preparation of daily chemicals.

[0048] In some embodiments of the present application, the addition amount of the self-assembled supramolecular modified chitosan composite material to the daily chemical product is 0.1 to 15 wt %.

[0049] Compared with the prior art, this application has the following beneficial effects:

[0050] The present application provides a self-assembled supramolecular modified chitosan composite material and a preparation method and application thereof. In the present application, carboxymethyl deacetylated chitosan and sodium bentonite modified by a cationic polymer are compounded. During the mixing process, the carboxymethyl deacetylated chitosan and the sodium bentonite modified by a cationic polymer undergo supramolecular self-assembly, and the carboxymethyl deacetylated chitosan is intercalated into the sodium bentonite modified by the cationic polymer in an orderly manner to obtain a self-assembled supramolecular modified chitosan composite material. In the self-assembled supramolecular modified chitosan composite material of the present application, after the bentonite is modified, not only the interlayer spacing of the bentonite becomes larger, but also the surface of the bentonite carries a certain positive charge, so that after the bentonite is subsequently assembled with the carboxymethyl deacetylated chitosan, there is a synergistic effect between the sodium bentonite modified by the cationic polymer and the carboxymethyl deacetylated chitosan, and the final product shows a good effect of improving scalp microecology, repairing skin and reducing skin inflammation. BRIEF DESCRIPTION OF THE DRAWINGS

[0051] Figure 1 This is a scanning electron microscope image of the self-assembled supramolecular modified chitosan composite material prepared in Example 1. DETAILED DESCRIPTION

[0052] In order to better illustrate the purpose, technical solutions and advantages of the present application, the present application will be further described below in conjunction with the accompanying drawings and specific embodiments.

[0053] In the following examples and comparative examples, the experimental methods used are conventional methods unless otherwise specified, and the materials, reagents, etc. used are all commercially available unless otherwise specified, and the components and raw materials used in each parallel experiment are of the same type.

[0054] Unless otherwise specified, all percentages mentioned in this application are by mass percentages.

[0055] The bentonite used in this application is commercially available common bentonite.

[0056] The carboxymethyl deacetylated chitosan used in the examples and comparative examples of the present application and the chitosan in the comparative examples are all sourced from Guangdong Zhongyan Zhijue Technology Co., Ltd. Carboxymethyl deacetylated chitosan obtained from other sources that meets the molecular weight and deacetylation degree of the present application can be used in the present application.

[0057] The polyquaternium-11, polyquaternium-16, polyquaternium-24, polyquaternium-28, polyquaternium-37, and polyquaternium-73 used in this application are from Dongguan Giant Microbiology Technology Co., Ltd.

[0058] Example 1: A self-assembled supramolecular modified chitosan composite material and its preparation method

[0059] This embodiment provides a self-assembled supramolecular modified chitosan composite material, comprising the following components in percentage by mass: 0.4% sodium bentonite modified by a cationic polymer, 17% carboxymethyl deacetylated chitosan, and 82.6% deionized water.

[0060] The particle size of the sodium bentonite modified by the cationic polymer is 50 μm, the weight average molecular weight of the carboxymethyl deacetylated chitosan is 130±2 kDa (about 130 kDa), and the deacetylation degree is 80±3% (about 80%).

[0061] The preparation method of the self-assembled supramolecular modified chitosan composite material is as follows:

[0062] (1) mixing water and carboxymethyl deacetylated chitosan uniformly to obtain a carboxymethyl deacetylated chitosan solution;

[0063] (2) Adding cationic polymer-modified sodium bentonite to the carboxymethyl deacetylated chitosan solution, mixing well, subjecting the mixture to high-speed shear dispersion treatment at 9000 rpm for 30 min, and then ultrasonic treatment at 500 W for 60 min to obtain a self-assembled supramolecular modified chitosan composite material.

[0064] Wherein, the preparation method of cationic polymer modified sodium bentonite is:

[0065] 1) Mix commercially available bentonite with 6 times the mass of water, stir at 120 rpm for 60 min, let stand for 90 min, and remove the upper solution to obtain washed bentonite;

[0066] 2) adding 6 times by mass of 2 mol / L sodium chloride solution to the washed bentonite, stirring at 120 rpm for 4 h and then standing for 90 min, removing the upper layer of sodium chloride solution to obtain sodium bentonite;

[0067] 3) Add 6 times by mass of 1 wt% polyquaternium-16 solution to the sodium bentonite, stir at 120 rpm for 4 h and then stand for 90 min, remove the upper layer of polyquaternium-16 solution, and then calcine at 160° C. for 120 min, and obtain cationic polymer-modified sodium bentonite after ball milling.

[0068] The scanning electron microscopy images of the self-assembled supramolecular modified chitosan composites are shown in Figure 1 As shown, the self-assembled supramolecular modified chitosan composite materials of the other embodiments are Figure 1 similar.

[0069] Example 2: A self-assembled supramolecular modified chitosan composite material and its preparation method

[0070] This embodiment provides a self-assembled supramolecular modified chitosan composite material, comprising the following components in percentage by mass: 0.2% sodium bentonite modified by a cationic polymer, 10% carboxymethyl deacetylated chitosan, and 89.8% deionized water.

[0071] The particle size of the sodium bentonite modified by the cationic polymer is 80 μm, the weight average molecular weight of the carboxymethyl deacetylated chitosan is 105±2 kDa (about 105 kDa), and the deacetylation degree is 75±3% (about 75%).

[0072] The preparation method of the self-assembled supramolecular modified chitosan composite material is as follows:

[0073] (1) mixing water and carboxymethyl deacetylated chitosan uniformly to obtain a carboxymethyl deacetylated chitosan solution;

[0074] (2) Adding cationic polymer-modified sodium bentonite to the carboxymethyl deacetylated chitosan solution, mixing well, subjecting the mixture to high-speed shear dispersion treatment at 12000 rpm for 20 min, and then ultrasonic treatment at 800 W for 40 min to obtain a self-assembled supramolecular modified chitosan composite material.

[0075] Wherein, the preparation method of cationic polymer modified sodium bentonite is:

[0076] 1) Mixing bentonite with 4 times the mass of water, stirring at 150 rpm for 30 min and then standing for 120 min, removing the upper layer solution to obtain washed bentonite;

[0077] 2) adding 4 times by mass of 0.5 mol / L sodium sulfate solution to the washed bentonite, stirring at 150 rpm for 3 h, and then standing for 120 min, removing the upper layer of sodium sulfate solution to obtain sodium bentonite;

[0078] 3) Add 4 times the mass of 1.8wt% polyquaternium-11 solution to the sodium bentonite, stir at 150rpm for 3h and then stand for 120min, remove the upper layer of polyquaternium-11 solution, and then calcine at 200°C for 90min, and obtain cationic polymer-modified sodium bentonite after ball milling.

[0079] Example 3: A self-assembled supramolecular modified chitosan composite material and its preparation method

[0080] This embodiment provides a self-assembled supramolecular modified chitosan composite material, comprising the following components in percentage by mass: 1.0% sodium bentonite modified by a cationic polymer, 20% carboxymethyl deacetylated chitosan, and 79.0% deionized water.

[0081] The particle size of the sodium bentonite modified by the cationic polymer is 30 μm, the weight average molecular weight of the carboxymethyl deacetylated chitosan is 175±2 kDa (about 175 kDa), and the degree of deacetylation is 80±3% (about 80%).

[0082] The preparation method of the self-assembled supramolecular modified chitosan composite material is as follows:

[0083] (1) mixing water and carboxymethyl deacetylated chitosan uniformly to obtain a carboxymethyl deacetylated chitosan solution;

[0084] (2) Adding cationic polymer-modified sodium bentonite to the carboxymethyl deacetylated chitosan solution, mixing well, subjecting the mixture to high-speed shear dispersion treatment at 6000 rpm for 40 min, and then ultrasonic treatment at 400 W for 80 min to obtain a self-assembled supramolecular modified chitosan composite material.

[0085] Wherein, the preparation method of cationic polymer modified sodium bentonite is:

[0086] 1) Mixing bentonite with 8 times the mass of water, stirring at 80 rpm for 90 min and then standing for 60 min, removing the upper layer solution to obtain washed bentonite;

[0087] 2) adding 8 times by weight of 1 mol / L sodium nitrate solution to the washed bentonite, stirring at 80 rpm for 5 h and then standing for 60 min, removing the upper layer of sodium sulfate solution to obtain sodium bentonite;

[0088] 3) Add 8 times by mass of 0.8 wt% polyquaternium-73 solution to the sodium bentonite, stir at 80 rpm for 5 h and then stand for 60 min, remove the upper layer of polyquaternium-73 solution, and then calcine at 130° C. for 150 min, and obtain cationic polymer-modified sodium bentonite after ball milling.

[0089] Embodiments 4-5: A self-assembled supramolecular modified chitosan composite material and its preparation method

[0090] Examples 4 and 5 provide a self-assembled supramolecular modified chitosan composite material, wherein the preparation method of the self-assembled supramolecular modified chitosan composite material and the sodium bentonite modified by the cationic polymer is the same as that of Example 1. The only difference is that some parameters of the carboxymethyl deacetylated chitosan are different from those of Example 1, and the differences are shown in Table 1 below.

[0091] Table 1

[0092]

[0093] Examples 6 to 11: A self-assembled supramolecular modified chitosan composite material and its preparation method

[0094] Examples 6 to 11 provide a self-assembled supramolecular modified chitosan composite material and a preparation method thereof, wherein the amount and particle size of the sodium bentonite modified by the cationic polymer, the amount, molecular weight and degree of deacetylation of the carboxymethyl deacetylated chitosan in the self-assembled supramolecular modified chitosan composite material are the same as those in Example 1. The difference is that the preparation method of the sodium bentonite modified by the cationic polymer is different from that in Example 1. The differences between the preparation method of the sodium bentonite modified by the cationic polymer and that in Example 1 are shown in Table 2 below.

[0095] Table 2

[0096]

[0097]

[0098] Comparative Example 1

[0099] The difference between this comparative example and Example 1 is that the preparation method of the self-assembled supramolecular modified chitosan composite material is different. The preparation method of the self-assembled supramolecular modified chitosan composite material is:

[0100] (1) mixing water and carboxymethyl deacetylated chitosan uniformly to obtain a carboxymethyl deacetylated chitosan solution;

[0101] (2) Adding cationic polymer-modified sodium bentonite (prepared by the same method as in Example 1) to the carboxymethyl deacetylated chitosan solution, mixing, mixing evenly at 150 rpm, and then ultrasonically treating at 500 W for 60 min to obtain a self-assembled supramolecular modified chitosan composite material.

[0102] Comparative Example 2

[0103] The difference between the self-assembled supramolecular modified chitosan composite material of this comparative example and Example 1 is that the carboxymethyl deacetylated chitosan in Example 1 is replaced by ordinary chitosan (the weight average molecular weight of chitosan is 130±2 kDa and the degree of deacetylation is 80±3%) in Comparative Example 2, and the remaining steps and parameters are the same as in Example 1.

[0104] Comparative Example 3

[0105] The difference between the self-assembled supramolecular modified chitosan composite material of this comparative example and Example 1 is that, in Comparative Example 3, the carboxymethyl deacetylated chitosan with a deacetylation degree of 80±3% in Example 1 is replaced by carboxymethyl deacetylated chitosan with a deacetylation degree of 99±1% (the deacetylation degree is about 100%), the molecular weight of the carboxymethyl deacetylated chitosan remains unchanged, and the remaining steps and parameters are the same as in Example 1.

[0106] Comparative Example 4

[0107] The self-assembled supramolecular modified chitosan composite material of this comparative example is different from that of Example 1 in that, in Comparative Example 4, the carboxymethyl deacetylated chitosan with a weight average molecular weight of 130±2 kDa in Example 1 is replaced with carboxymethyl deacetylated chitosan with a weight average molecular weight of 220±2 kDa, the deacetylation degree of the carboxymethyl deacetylated chitosan remains unchanged, and the remaining steps and parameters are the same as those of Example 1.

[0108] Comparative Example 5

[0109] The difference between the self-assembled supramolecular modified chitosan composite material of this comparative example and Example 1 is that in Comparative Example 5, the sodium bentonite modified by the cationic polymer in Example 1 is replaced by commercially available ordinary bentonite (ball-milled to a particle size of 50 μm), and the remaining steps and parameters are the same as in Example 1.

[0110] Comparative Example 6

[0111] The self-assembled supramolecular modified chitosan composite material of this comparative example is different from that of Example 1 in that the preparation method of the sodium-modified bentonite modified by the cationic polymer is different. The sodium-modified bentonite modified by the cationic polymer of Comparative Example 6 is not subjected to the sodium treatment of step 2).

[0112] Comparative Example 7

[0113] The self-assembled supramolecular modified chitosan composite material of this comparative example is different from that of Example 1 in that the preparation method of the cationic polymer modified sodium bentonite is different. The cationic polymer modified sodium bentonite of Comparative Example 7 is not subjected to the cationic polymer modification treatment of step 3).

[0114] Comparative Example 8

[0115] The self-assembled supramolecular modified chitosan composite material of this comparative example is different from that of Example 1 in that the preparation method of the sodium bentonite modified by the cationic polymer is different. The sodium bentonite modified by the cationic polymer of Comparative Example 8 is not subjected to the high temperature calcination treatment of step 3).

[0116] Comparative Example 9

[0117] The difference between the self-assembled supramolecular modified chitosan composite material of this comparative example and Example 1 is that the preparation method of the sodium bentonite modified by the cationic polymer is different. In Comparative Example 9, the sodium chloride in step 2) is replaced with 0.5 mol / L sodium carbonate, and the remaining steps and parameters are the same as in Example 1.

[0118] Comparative Example 10

[0119] The self-assembled supramolecular modified chitosan composite material of this comparative example is different from that of Example 1 in that the preparation method of the sodium bentonite modified by the cationic polymer is different. In Comparative Example 10, the 1wt% polyquaternium-16 solution in step 3) is replaced with a 3wt% polyquaternium-16 solution, and the remaining steps and parameters are the same as those of Example 1.

[0120] Comparative Example 11

[0121] The difference between the self-assembled supramolecular modified chitosan composite material of this comparative example and Example 1 is that the preparation method of the sodium bentonite modified by the cationic polymer is different. Comparative Example 11 replaces the 1wt% polyquaternium salt-16 solution in step B3 with a 1wt% hexadecyltrimethylammonium chloride solution, and the remaining steps and parameters are the same as Example 1.

[0122] Comparative Example 12

[0123] The difference between the self-assembled supramolecular modified chitosan composite material of this comparative example and Example 1 is that the preparation method of the sodium bentonite modified by the cationic polymer is different. In comparative example 12, the calcination temperature in step 3) is changed from 160°C to 250°C, and the remaining steps and parameters are the same as in Example 1.

[0124] Test Example 1: Stability Test

[0125] Test samples: the self-assembled supramolecular modified chitosan composite materials prepared in Examples 1 to 11 and the materials prepared in Comparative Examples 1 to 12.

[0126] Test steps: Place the test sample at 25°C for 28 days to conduct a room temperature stability test (No. 1); place the test sample at -17°C for 7 days, return to room temperature, and then place it at 45°C for 7 days, repeat the above operation, and finally return to room temperature to conduct a high and low temperature cycle stability test (No. 2). After 28 days, if the appearance of the test sample in the two stability tests has not changed, it is considered to have passed.

[0127] The test results are shown in Table 3 below.

[0128] Table 3

[0129]

[0130]

[0131] The test results show that the self-assembled supramolecular modified chitosan composite materials of the embodiments of the present invention have good stability and have passed the 28-day room temperature stability test and the high and low temperature cycle stability test.

[0132] The self-assembled supramolecular modified chitosan composite material of Comparative Example 1 was not subjected to high-speed shear treatment during preparation, and the mixing of the sodium bentonite modified by the cationic polymer and the modified chitosan was uneven. The sodium bentonite modified by the cationic polymer and the modified chitosan could not self-assemble to form supramolecular materials, resulting in the precipitation of the sodium bentonite modified by the cationic polymer, and the appearance of precipitates at the bottom. Comparative Example 3 changed the degree of deacetylation of the carboxymethyl deacetylated chitosan. After the carboxymethyl deacetylated chitosan was mixed with the sodium bentonite modified by the cationic polymer, it was unstable under high temperature conditions. Comparative Example 4 used carboxymethyl deacetylated chitosan with a larger molecular weight to prepare the self-assembled supramolecular modified chitosan composite material. The high molecular weight carboxymethyl deacetylated chitosan was easy to solidify at low temperature. Therefore, at -17°C, the self-assembled supramolecular modified chitosan composite material solidified. Comparative Example 5 uses commercially available bentonite to form a self-assembled supramolecular modified chitosan composite material. The commercially available bentonite has not been modified, and the interlayer spacing in the bentonite is small, which is not conducive to the intercalation of carboxymethyl deacetylated chitosan, and the final product is prone to instability. Comparative Example 6 has not been treated with sodium, and Comparative Example 8 has not been treated with high-temperature calcination. The interlayer spacing in the bentonite is still small, which is not conducive to the intercalation of carboxymethyl deacetylated chitosan, and the final product is unstable. Comparative Example 10 changes the concentration of the cationic polymer and Comparative Example 11 changes the type of the cationic polymer. The changes in the above two conditions are likely to cause product instability.

[0133] Test Example 2: Scalp Microecology Test

[0134] Test samples: the self-assembled supramolecular modified chitosan composite materials prepared in Examples 1 to 11 and the materials prepared in Comparative Examples 1 to 12.

[0135] Test method: 2002 edition of "Technical Specifications for Disinfection" - 2.1.8.3 Minimum inhibitory concentration test (agar dilution method).

[0136] Test strains: Test strains: Staphylococcus epidermidis ATCC 12228; Propionibacterium acnes ATCC 11827; Malassezia furfur ATCC 44344, all from Guangdong Institute of Microbiology.

[0137] Table 4

[0138]

[0139]

[0140] Staphylococcus epidermidis is the main component of the normal commensal flora of healthy people's skin. It not only resists potential pathogenic microorganisms, but also inhibits the overgrowth of existing conditional pathogens. Propionibacterium acnes is the dominant flora on the skin, living in hair follicles and sebaceous glands. Propionibacterium acnes is one of the causes of acne. Malassezia furfur is an important factor in inducing or aggravating diseases such as seborrheic dermatitis, hair loss, pityriasis capitis, folliculitis, pruritus, and tinea capitis.

[0141] As shown in Table 4 above, the antibacterial concentration of the self-assembled supramolecular modified chitosan composite material of the embodiment of the present invention against Staphylococcus epidermidis is >100000 mg / kg, the minimum inhibitory concentration against Propionibacterium acnes is <9200 mg / kg, and the minimum inhibitory concentration against Malassezia furfur is <3800 mg / kg, indicating that the self-assembled supramolecular modified chitosan composite material of the embodiment of the present invention does not inhibit the colonization of normal skin flora, inhibits the reproduction of harmful flora, and has a good effect of regulating microecology.

[0142] The self-assembled supramolecular modified chitosan composite material of Comparative Example 1 was not subjected to high-speed shear dispersion during the preparation process. During the formation of the modified chitosan composite material, the self-assembly effect of the sodium bentonite modified by the cationic polymer and the modified chitosan was poor, resulting in a poor antibacterial effect of the final product on Propionibacterium acnes and Malassezia furfur. Comparative Example 2 used unmodified chitosan and modified bentonite for combination. The unmodified chitosan itself had a poor antibacterial effect, and its compatibility with the modified bentonite was poor, resulting in a poor antibacterial effect of the final product.

[0143] Comparative Example 3 changes the deacetylation degree of carboxymethyl deacetylated chitosan, the amino groups on the molecular weight of the polysaccharide in carboxymethyl deacetylated chitosan change, and the properties of carboxymethyl deacetylated chitosan change, resulting in a poor antibacterial effect of the final product on Propionibacterium acnes and Malassezia furfur.

[0144] In Comparative Example 4, the molecular weight of carboxymethyl deacetylated chitosan was changed, and the antibacterial effect of the final product on Propionibacterium acnes and Malassezia furfur became worse, indicating that carboxymethyl deacetylated chitosan with a weight average molecular weight of 100 kDa to 180 kDa is preferred in the present invention.

[0145] Comparative Examples 5 to 8 have poor antibacterial effects on Propionibacterium acnes and Malassezia furfur, indicating that the modified chitosan composite material obtained by self-assembly with carboxymethyl deacetylated chitosan after the bentonite modification treatment has a good effect of regulating microecology. In the present invention, the bentonite needs to be treated with sodium, cationic polymer modification and high-temperature calcination, and the modified chitosan composite material prepared by the obtained bentonite has a good effect of regulating microecology. Comparative Example 9 uses a slightly alkaline sodium salt solution for sodium treatment. When it is treated later, the effect of the modification of the cationic polymer will be weakened, resulting in a poor antibacterial effect of the final product on Propionibacterium acnes and Malassezia furfur.

[0146] Comparative Example 10 changes the concentration of the cationic polymer, and Comparative Example 11 changes the type of cationic polymer. The final modified chitosan composite material exhibits an inhibitory effect on Staphylococcus epidermidis, and the inhibitory effect on Propionibacterium acnes and Malassezia furfur becomes weaker, indicating that during the cationic modification process, the concentration and type of the cationic polymer have a great influence on the effect of the final product in regulating the microecology. If the concentration of the cationic polymer is low, the modification effect is poor, but if the concentration of the cationic polymer is too high, the cationic polymer attached to the surface of the modified bentonite will increase, affecting the subsequent intercalation of carboxymethyl deacetylated chitosan.

[0147] In the present invention, the concentration of the cationic polymer is preferably 0.5-2wt%, and the type of the cationic polymer is preferably polyquaternium salt. Comparative Example 12 changes the calcination temperature in the preparation process of the sodium bentonite modified by the cationic polymer. Under the condition of elevated temperature, the cationic polymer attached to the surface of the bentonite is easily evaporated or even carbonized under high temperature conditions, resulting in a weakened inhibitory effect of the final product on Propionibacterium acnes and Malassezia furfur, and a poor effect of the final product in regulating the microecology.

[0148] Test Example 3: Anti-inflammatory effect test

[0149] Inflammation is one of the most common clinical diseases. It is a defense response of the human body to ensure the removal of harmful stimuli and repair of damaged tissues. When human immune cells are affected by inflammatory factors, some small molecular weight soluble proteins or polypeptides that can transmit information between cells and have specific immune regulation functions are secreted by the body itself and can participate in or cause inflammatory reactions. These substances are called inflammatory factors, including NO, TNF-ɑ, IL-6, IL-8, etc. These inflammatory factors have direct or indirect effects on cellular inflammation.

[0150] This test used LPS-induced mouse fibroblasts L929 as an in vitro inflammatory cell model and measured the relative mRNA expression of inflammatory factors (IL-8) to evaluate whether the test substance had in vitro anti-inflammatory effects.

[0151] Test samples: the self-assembled supramolecular modified chitosan composite materials prepared in Examples 1 to 11 and the materials prepared in Comparative Examples 1 to 12 were prepared into solutions with a mass concentration of 1 wt % using H-DMEM culture medium containing 10 % FBS.

[0152] Test steps: Take L929 cells in the logarithmic phase and add 2×10 5 cells, add H-DMEM medium containing 10% FBS (referred to as culture medium) and incubate at 37°C and 5% CO 2 , cultured in a saturated humidity environment for 24 hours; aspirate the culture medium, add 1 mL of culture medium to the negative control group, add 1 mL of 5 μg / mL LPS solution to the model control group and the sample group to be tested for 18 hours to induce modeling, aspirate the culture medium, add 1 mL of culture medium to the negative control group and the model control group, add 1 mL of the corresponding sample solution to each sample group, and continue to culture for 24 hours. After the culture, extract the total RNA of L929 cells in each well, reverse transcribe and perform fluorescence quantitative PCR, and the real-time fluorescence quantitative results are used Method to calculate.

[0153] The test results are shown in Table 5 below:

[0154] Table 5

[0155]

[0156] After induction treatment with LPS solution, compared with the negative control group, the relative expression of IL-8mRNA in the model control group increased rapidly, indicating that the IL-8 inflammatory factor produced in L929 cells increased, and after the self-assembled supramolecular modified chitosan composite material of the embodiment or comparative example was added to the test sample group, the relative expression of IL-8mRNA decreased, the production of inflammatory factors decreased, and the test sample showed a certain anti-inflammatory effect. Among them, the relative expression of IL-8mRNA in Examples 1 to 11 was lower than that in Comparative Examples 1 to 12, indicating that the anti-inflammatory effect of Examples 1 to 11 was better than that of Comparative Examples 1 to 12. The anti-inflammatory effect of Example 1 is better than that of Comparative Example 1, indicating that the preparation steps of the self-assembled supramolecular modified chitosan composite material have a great influence on the anti-inflammatory effect of the final product. The self-assembled supramolecular modified chitosan composite material of Comparative Example 1 was not subjected to high-speed shear dispersion during the preparation process. In the formation process of the modified chitosan composite material, the self-assembly effect of the sodium bentonite modified by the cationic polymer and the modified chitosan was not good, resulting in a poor anti-inflammatory effect of the final product.

[0157] The anti-inflammatory effect of Example 1 is better than that of Comparative Examples 2 to 4, indicating that the type of chitosan, the molecular weight of the modified chitosan and the degree of deacetylation have a great influence on the effect of the final product. The modified chitosan of the present invention is preferably carboxymethyl deacetylated chitosan, the weight average molecular weight of the modified chitosan is preferably 100 kDa to 180 kDa, and the degree of deacetylation is preferably between 70 and 95%.

[0158] The anti-inflammatory effect of Example 1 is better than that of Comparative Examples 5 to 8, indicating that the modification of bentonite has a great influence on the anti-inflammatory effect of the final product. In the present invention, commercially available bentonite needs to be treated with sodium, cationic polymer modification and high-temperature calcination before it can be used to prepare self-assembled supramolecular modified chitosan composite materials. If one of these steps is missing, the anti-inflammatory effect of the final product is poor.

[0159] The anti-inflammatory effect of Example 1 is better than that of Comparative Example 9, indicating that in the sodium treatment, a neutral sodium salt solution is required for the sodium treatment. Using a slightly alkaline sodium salt solution for the sodium treatment will weaken the effect of the subsequent cationic polymer modification, resulting in a poor anti-inflammatory effect of the final product. The anti-inflammatory effect of Example 1 is better than that of Comparative Examples 10 to 11, indicating that during the cationic polymer modification process, the type of cationic polymer and the concentration of the cationic polymer solution during the modification process have an impact on the anti-inflammatory effect of the final product. In the present invention, the concentration of the cationic polymer is preferably 0.5 to 2 wt%, and the type of the cationic polymer is preferably polyquaternary ammonium salt.

[0160] The anti-inflammatory effect of Example 1 is better than that of Comparative Example 12, indicating that the calcination temperature in the preparation process of the cationic polymer-modified sodium bentonite will affect the anti-inflammatory effect of the final product. Under the condition of too high temperature, the cationic polymer attached to the surface of the bentonite is easy to evaporate or even denature under high temperature conditions, and the composite effect of the cationic polymer-modified sodium bentonite and the modified chitosan is deteriorated, and the anti-inflammatory effect of the final product is deteriorated. In the present invention, the calcination temperature is preferably 130 to 200°C.

[0161] Test Example 4: Repair Effect Test

[0162] SIRT1 is a nuclear protein that can deacetylate class III histones and interact with a variety of non-histone proteins and cytokines. It can also directly participate in transcriptional silencing, chromatin modification, and the regulation of cell meiotic cycle control points, enhance the ability to repair DNA double-strand damage, inhibit rDNA recombination, and increase genome stability, thereby delaying aging and inhibiting apoptosis.

[0163] In this study, 0.1 μg / mL H 2 O 2Keratinocytes HaCaT induced for 1 hour were used as an in vitro repair model, and the relative expression level of Sirt1 mRNA was measured to evaluate the repair effect of the test samples.

[0164] Test sample: Same as Test Example 3.

[0165] Test steps: HaCaT cells in the logarithmic phase were added to each well of a 6-well culture plate. 5 cells, add H-DMEM medium containing 10% FBS (referred to as culture medium) and incubate at 37°C and 5% CO 2 , cultured in a saturated humidity environment for 24 h; the culture medium was discarded, 1 mL of culture medium was added to the negative control group, and 1 mL of 0.1 μg / mL H 2 O 2 After induction for 1 hour, the culture medium was discarded, 1 mL of culture medium was added to the negative control group and the model control group, and 1 mL of the corresponding sample solution was added to each sample group, and the culture was continued for 24 hours. After the culture, the total RNA of HaCaT cells in each well was extracted and reverse transcribed for fluorescence quantitative PCR. The real-time fluorescence quantitative results were used Method to calculate.

[0166] Table 6

[0167]

[0168] The results are shown in Table 6. 2 O 2 After solution induction treatment, the relative expression of SIRT1 mRNA in the model control group decreased compared with the negative control group, indicating that HaCaT cells produced less SIRT1 and weakened the cell's ability to resist damage and repair. 2 O 2 After solution induction treatment, the relative expression of SIRT1 mRNA in the test sample increased to varying degrees, indicating that the cells produced more SIRT1 protein and had stronger resistance to damage and repair capabilities, and the test sample showed a repair effect.

[0169] The repair effect of Example 1 is better than that of Comparative Example 1, indicating that the preparation steps of the self-assembled supramolecular modified chitosan composite material have a great influence on the repair effect of the final product. The self-assembled supramolecular modified chitosan composite material of Comparative Example 1 did not undergo high-speed shear dispersion during the preparation process. During the formation of the modified chitosan composite material, the self-assembly effect of the sodium bentonite modified by the cationic polymer and the modified chitosan was not good, resulting in a poor repair effect of the final product.

[0170] The repair effect of Example 1 is better than that of Comparative Examples 2 to 4, indicating that the type of chitosan, the molecular weight of the modified chitosan and the degree of deacetylation have a great influence on the repair effect of the final product. In the present invention, the modified chitosan is preferably carboxymethyl deacetylated chitosan, the weight average molecular weight of the modified chitosan is preferably 100 kDa to 180 kDa, and the degree of deacetylation is preferably between 70 and 95%.

[0171] The repair effect of Example 1 is better than that of Comparative Examples 5 to 8, indicating that the modification of bentonite has a great influence on the repair effect of the final product. In the present invention, commercially available bentonite needs to be treated with sodium, cationic polymer and high-temperature calcination before it can be used to prepare self-assembled supramolecular modified chitosan composite materials. If one of these steps is missing, the repair effect of the final product is poor.

[0172] The repair effect of Example 1 is better than that of Comparative Example 9, which indicates that a neutral sodium salt solution is required for the sodium treatment. Using an alkaline sodium salt solution for the sodium treatment will weaken the effect of the subsequent cationic polymer modification, resulting in a poor repair effect of the final product.

[0173] The repair effect of Example 1 is better than that of Comparative Examples 10 to 11, indicating that during the cationic polymer modification process, the type of cationic polymer and the concentration of the cationic polymer solution during the modification process have an impact on the repair effect of the final product. In the present invention, the concentration of the cationic polymer is preferably 0.5 to 2 wt%, and the type of the cationic polymer is preferably polyquaternary ammonium salt.

[0174] The repair effect of Example 1 is better than that of Comparative Example 12, indicating that the calcination temperature in the preparation process of the cationic polymer-modified sodium bentonite will affect the repair effect of the final product. Under the condition of too high temperature, the cationic polymer attached to the surface of the bentonite is easy to evaporate or even denature under high temperature conditions, and the composite effect of the cationic polymer-modified sodium bentonite and the modified chitosan is deteriorated, and the repair effect of the final product is deteriorated. In the present invention, the calcination temperature is preferably 130 to 200°C.

[0175] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present application rather than to limit the scope of protection of the present application. Although the present application has been described in detail with reference to the preferred embodiments, ordinary technicians in this field should understand that the technical solution of the present application can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present application.

Claims

1. A self-assembled supramolecular modified chitosan composite material, characterized in that: In terms of mass percentage, the self-assembled supramolecular modified chitosan composite material comprises: 10-20% carboxymethyl deacetylated chitosan, 0.2-1.0% cationic polymer modified sodium bentonite and the balance water.

2. The self-assembled supramolecular modified chitosan composite material according to claim 1, characterized in that: The weight average molecular weight of the carboxymethyl deacetylated chitosan is 100 kDa to 180 kDa, and the deacetylation degree is 70 to 95%.

3. The self-assembled supramolecular modified chitosan composite material according to claim 1, characterized in that: The particle size of the sodium bentonite modified by the cationic polymer is 30 to 80 μm.

4. The self-assembled supramolecular modified chitosan composite material according to claim 1, characterized in that: The cationic polymer includes at least one of polyquaternium-11, polyquaternium-16, polyquaternium-24, polyquaternium-28, polyquaternium-37 and polyquaternium-73.

5. The self-assembled supramolecular modified chitosan composite material according to claim 1, characterized in that: The preparation method of the cationic polymer-modified sodium bentonite comprises the following steps: 1) Mixing bentonite with water, stirring and then standing, and removing the upper layer solution to obtain washed bentonite; 2) adding the sodium salt solution to the washed bentonite prepared in step 1), stirring and then standing, and removing the upper layer of solution to obtain sodium bentonite; 3) Soaking the sodium bentonite prepared in step 2) in a cationic polymer solution, stirring and then standing, removing the upper solution, and then calcining at high temperature and ball milling to obtain the cationic polymer-modified sodium bentonite.

6. The self-assembled supramolecular modified chitosan composite material according to claim 5, characterized in that: In step 1), the mass ratio of the bentonite to water is 1:(4-8); in step 2), the mass ratio of the washed bentonite to the sodium salt solution is 1:(4-8); in step 3), the mass ratio of the sodium bentonite to the cationic polymer solution is 1:(4-8).

7. The self-assembled supramolecular modified chitosan composite material according to claim 5, characterized in that: The concentration of sodium ions in the sodium salt solution is 1-3 mol / L, and the concentration of cationic polymer in the cationic polymer solution is 0.5-2 wt %.

8. The self-assembled supramolecular modified chitosan composite material according to claim 5, characterized in that: In the step 1), the stirring time is 30 to 90 minutes, the stirring speed is 80 to 150 rpm, and the standing time is 60 to 120 minutes; In the step 2) and step 3), the stirring time is 3 to 5 hours, the stirring speed is 80 to 150 rpm, and the standing time is 60 to 120 minutes; In the step 3), the calcination temperature is 130-200° C., and the calcination time is 90-150 min.

9. The method for preparing the self-assembled supramolecular modified chitosan composite material according to any one of claims 1 to 8, characterized in that: The following steps are involved: (1) mixing water and carboxymethyl deacetylated chitosan uniformly to obtain a carboxymethyl deacetylated chitosan solution; (2) mixing the carboxymethyl deacetylated chitosan solution and the sodium bentonite modified by the cationic polymer, and subjecting the mixture to high-speed shear dispersion treatment and ultrasonic treatment to obtain a self-assembled supramolecular modified chitosan composite material; The rotation speed of the high-speed shearing and dispersing treatment is 6000-12000 rpm, and the time of the high-speed shearing and dispersing treatment is 20-40 min; The power of the ultrasonic treatment is 400-800W, and the time of the ultrasonic treatment is 40-80min.

10. Use of the self-assembled supramolecular modified chitosan composite material according to any one of claims 1 to 8 in the preparation of daily chemicals.

Citation Information

Patent Citations

  • Environment-friendly modified bentonite and preparation method thereof

    CN101058426A

  • Production method of environment-friendly chitosan intercalation composite bentonite adsorbent

    CN101757886A

  • Preparation method of chitosan quaternary ammonium salt (HTCC) organic-intercalated montmorillonite (MMT) composite material

    CN110183773A

  • Micro-ecological scalp care composition and preparation method and application thereof

    CN111407683A

  • Manufacturing and applicaition methods of water dispersant which containing chitosan type cationic acrylamide copolymer

    KR1020050093731A